(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
The article is an attempt at philosophical reflection on the possibility of rational justification of religion and its place in today’s world by recreating Leszek Kołakowski’s intellectual path to the Absolute as a guarantor of the value and its apology of Christianity in this context. Following the movement of thoughts in works from Religious consciousness and The Church Bond through The Presence of Myth to Main Currents of Marxism, the author shows how Kołakowski came to the position that faith is an inalienable element of the human condition; we cannot believe it at all, only the objects of our faith can be different. Analyzing Kołakowski’s texts, taking into account their chronology, it can be seen that from the perspective of Marxism he tried to capture the essence of religion, while studying religion allowed him to see the features of religious thinking in Marxism. As a consequence, he noticed that faith, next to reason, is an indelible way of our knowledge, and the myth can be removed only by replacing it with another myth. The climax of this thinking seems to be Horror Metaphysicus – according to his own declaration – the opus magnum of Kołakowski. The author argues that the entire apology of Christianity, which dominates in the late philosophical activity of Kołakowski, should be understood in this context. The paper also shows why we should defend Christianity – even if, according to the author of The Presence of Myth, is one of the myths – as the best combination the individual and social dimension of our existence.